Anxiety, insomnia and family support in nurses, two years after the onset of the pandemic crisis - Christos Sikaras; Maria Tsironi; Sofia Zyga; Aspasia Panagiotou (AIMS Press, 2023)
Introduction: The Covid-19 pandemic continues to cause serious physical and mental problems for health professionals, particularly nurses. Aim: To estimate the prevalence of anxiety and insomnia and to evaluate their possible association with family support received by nurses two years after the onset of the pandemic. Materials and methods: In total, the study participants were 404 nurses (335 females and 69 males) with a mean age of 42.88 (SD = 10.9) years and a mean of 17.96 (SD = 12) years working as nurses. Nurses from five tertiary hospitals in Athens constituted the study population who completed the questionnaires State-Trait Anxiety Inventory (STAI), Athens Insomnia Scale (AIS) and Family Support Scale (FSS), in the months of November and December 2021. Regarding demographic and occupational characteristics, gender, age and years of experience as nurses were recorded. Results: 60.1% of the nurses showed abnormal scores in state anxiety, with 46.8% in trait anxiety, and 61.4% showed insomnia. Women showed higher scores on the two subscales of anxiety and the insomnia scale compared to men (p < 0.01 and p < 0.05 respectively), while they showed a lower score on the FSS without statistical significance (p > 0.05). Positive correlations (p < 0.01) were found between the State Anxiety Inventory, Trait Anxiety Inventory and AIS, while all of them showed a high negative correlation with FSS (p < 0.01). Age showed a negative correlation with Trait Anxiety Inventory (p < 0.05). As shown by the mediation analysis, the relationship between state anxiety and insomnia was mediated by trait anxiety, whereas state anxiety appeared to be dependent on family support. Conclusions: Nurses continue to experience high levels of anxiety and insomnia and feel less supported by their families than in the first year of the pandemic. Insomnia appears to be dependent on state anxiety, with a significant indirect effect of trait anxiety, while family support seems to affect state anxiety.